2006
DOI: 10.1097/01.aids.0000233574.49220.de
|View full text |Cite
|
Sign up to set email alerts
|

Sustained improvement of dyslipidaemia in HAART-treated patients replacing stavudine with tenofovir

Abstract: The substitution of tenofovir for stavudine causes a sustained improvement of dyslipidaemia. The reduction, although modest, is robust and sustained over time, and significantly reduces the CVR. This switch strategy is safe and contributes to an improvement in the lipid profile, especially TG, in HAART-treated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 35 publications
3
43
1
3
Order By: Relevance
“…This observation is also consistent with PI to NNRTI switch studies which demonstrate that switching from PI-based regimens to NVP-based therapy may offer greater lipid improvements than switching the PI component to EFV [1,7,9,[14][15][16][17] . Taken together, these data highlight the important differences in the magnitude of dyslipidemia associated with EFV and NVP and would also suggest that the potential for an intra-NNRTI switch strategy for improvement of EFV-associated dyslipidemia may [6][7][8][9][10][11] . Our observations are consistent with one report that evaluated the lipid effects in patients who had experienced psychiatric side effects and were switched from EFV to NVP [12] .…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…This observation is also consistent with PI to NNRTI switch studies which demonstrate that switching from PI-based regimens to NVP-based therapy may offer greater lipid improvements than switching the PI component to EFV [1,7,9,[14][15][16][17] . Taken together, these data highlight the important differences in the magnitude of dyslipidemia associated with EFV and NVP and would also suggest that the potential for an intra-NNRTI switch strategy for improvement of EFV-associated dyslipidemia may [6][7][8][9][10][11] . Our observations are consistent with one report that evaluated the lipid effects in patients who had experienced psychiatric side effects and were switched from EFV to NVP [12] .…”
Section: Resultsmentioning
confidence: 71%
“…Prospective comparisons of nevirapine (NVP) and EFV have demonstrated that EFV-based HAART is associated with greater elevation in total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), triglycerides (TG) and non-HDL cholesterol (non-HDL-C) as well as l increase in high-density lipoprotein (HDL-C) of lesser magnitude when compared to NVPbased HAART [4][5][6] . Antiretroviral switch strategies, in addition to traditional lipid-lowering treatment approaches, have proven to be useful in select patients with PI and thymidine analogue-associated dyslipidemia [1,[7][8][9][10][11] . Two studies have shown improvements in lipids when switching EFV to NVP [12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…Among NRTIs, tenofovir may be associated with less aggravation in the lipoprotein profi le compared with stavudine. 30 Some studies report that NRTI therapy may be related to mitochondrial toxicity, resulting in lactic acidosis. [31][32][33] The dyslipidemic pattern has most commonly been reported among patients receiving PIs.…”
Section: Introductionmentioning
confidence: 99%
“…A concentração sérica diminuída de HDL-c pode ser utilizada como marcador de atividade inflamatória crônica (LLIBRE et al, 2006 (LACHGAR et al 1999;PYO et al, 2008), através da geração mitocondrial de ânion superóxido que pode, por sua vez, ativar o fator de transcrição nuclear NF-k B e induzir a expressão e replicação do HIV (ALLARD et al 1998;MANDAS et al, 2009 Vários estudos em humanos têm relatado que os flavonóides do cacau podem melhorar o perfil lipídico e outros marcadores cardiovasculares (OSAKABE et al 2001;MURSU et al, 2004;JIA et al 2010). Tais benefícios podem ser atribuídos a propriedades antioxidantes dos flavonóides, com provável diminuição do EO nos tecidos (OSAKABE et al 2001;MURSU et al, 2004;JIA et al 2010).…”
Section: Terapia Antirretroviral E Alterações Lipídicasunclassified
“…Os medicamentos desta classe podem diminuir a lipogênese e diferenciação de adipócitos no tecido subcutâneo, sendo uma das possíveis causas da toxicidade mitocondrial, inibindo a DNA polimerase  mitocondrial e esgotando o DNA mitocondrial (LLIBRE et al, 2006;TUNGSIRIPAT et al, 2010). As mitocôndrias são sítios susceptíveis ao EO devido à capacidade de gerar EROS (LEWIS et al, 2003).…”
Section: Análise Laboratorialunclassified